Healthy Lifestyle Education for Prevention of Pulmonary TB at Sialang Health Center - Gurusinga, Rahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pulmonary Tuberculosis is a contagious infectious disease caused by the bacteria Mycobacterium tuberculosis and attacks the lungs. Pulmonary TB is spread through phlegm droplets that come out when the sufferer coughs, sneezes, or talks. This disease is characterized by the main symptoms of a cough with phlegm that lasts for more than two weeks, sometimes accompanied by blood, fever, night sweats, weight loss, and weakness. Pulmonary TB is a serious public health problem because of its high transmission rate and can cause serious complications if not treated properly. Prevention and control of Pulmonary TB can be done through early detection, regular and complete treatment, and the implementation of clean and healthy living behaviors. Educational activities on healthy living behavior for the prevention of Pulmonary Tuberculosis were carried out at the Sialang Health Center, involving families and Pulmonary TB sufferers. The implementation of the activity used lecture methods, discussions, and the provision of educational media on the prevention of Pulmonary Tuberculosis. From the results of the activity, there was an increase in public knowledge about the prevention of Pulmonary Tuberculosis, namely from 55% before education to 85% after education. This increase was also accompanied by improvements in the attitudes and behavior of participants, such as being more active in using masks when coughing, maintaining home ventilation, maintaining personal hygiene, and seeking health services earlier if symptoms suspected of Pulmonary Tuberculosis appear. Participants also showed a better understanding of symptoms, transmission methods, and the importance of maintaining healthy living behavior in the family and community environment. This proves that education that is carried out in a structured and interactive manner can be an effective means of increasing public awareness and knowledge. Thus, education is an important and inexpensive approach that can improve the quality of life and create a healthy, independent, and prosperous society.